Redesigning Financial Governance for the New Global Economy of the 21st Century - Passaris, Constantine (Journal of Comparative International Management, 2011)
The mission and mandate of economic governance and its accompanying institutional architecture requires realignment in order to conform to the realities of the new global economy of the 21st century. Two recent economic events, the emergence of the new economy and the aftermath of the financial crisis of 2008, have become the defining milestones which precipitated the need for a new vision and a new direction for the financial governance. The new global economy of the 21st century is composed of a trilogy of interactive forces that include globalization, trade liberalization and the information technology and communications revolution. The aftermath of the financial crisis has precipitated a more interventionist role for government and has laid the foundations for new institutional and regulatory structures that will impact on the financial landscape of the 21st century. This paper explores the future architectural governance landscape for the financial industry and the scope and substance of regulatory initiatives and mechanisms that should be designed in order to avert a future financial crisis.